Analysis of employee performance improvement strategies in a company - Wati, Agustina; Aulia, Sinta Nurngaini; Wahyudi, Wahyudi (Jurnal Mantik, 2024)
Today's modern era requires companies to adjust their strategies to stay alive and survive as changes continue. To survive, a company's most valuable asset is its human resources. Human resources are assets that play a significant role in a company. Even though there are many tools in a company, without the support of human resources, it will not run optimally. To achieve a company's goals, employees must maximize their performance potential properly. The purpose of this study is to explain how to improve employee performance in a company; strategies to improve employee performance in a company in this study are general; this type of research is a qualitative literature study. The study results show that employees play an essential role in the company; therefore, improving their performance requires a good strategy: training and education, discipline, enforcement of rules, punishment, compensation and reward, and performance evaluation